Surface plasmon polariton modes propagating along the periodically corrugated boundary of a metamaterial - Cuevas, Mauro (2010)
We present a perturbative treatment to find the surface plasmon polariton modes corresponding to the free oscillations of the electromagnetic field on a cylindrical periodic interface that separates a conventional dielectric medium and a metamaterial with arbitrary values of the constitutive parameters. The method is used to investigate how a shallow sinusoidal corrugation affects the propagation constants and the electromagnetic field distributions of the modes obtained for a flat interface. We provide numerical results which are in complete agreement with the results obtained from the study of the complementary scattering problem, as well as showing field distributions radically different from those obtained for the well known case of corrugated metals. © c EDP Sciences, Società Italiana di Fisica, Springer-Verlag 2010.